2019
DOI: 10.2147/ijn.s192520
|View full text |Cite
|
Sign up to set email alerts
|

<p>Development of anisamide-targeted PEGylated gold nanorods to deliver epirubicin for chemo-photothermal therapy in tumor-bearing mice</p>

Abstract: Background Gold nanorods (AuNRs), due to the optical and electronic properties namely the surface plasma resonance, have been developed to achieve the light-mediated photothermal therapy (PTT) for cancer. However, PTT alone may suffer from inefficient tumor killing. Recently, the combination of PTT and chemotherapy has been utilized to achieve synergistic anticancer effects. Methods In this study, AuNRs capped with hexadecyltrimethylammonium bromide (CTAB), poly(acrylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The surface of Au 800 ‐CTAB‐PAA‐PEG‐AA was coated with epirubicin (EPI), an anthracycline drug, through electrostatic interaction resulting in the formation of the Au 800 ‐CTAB‐PAA‐PEG‐AA.EPI complex. The findings confirmed that the chemotherapeutic agent was released on a pH‐dependent basis, that nuclear trafficking of EPI was assisted, and that antiproliferative effects in PC‐3 cells were induced [100].…”
Section: Application Of Hybrid Nps Against Different Type Of Cancersmentioning
confidence: 53%
“…The surface of Au 800 ‐CTAB‐PAA‐PEG‐AA was coated with epirubicin (EPI), an anthracycline drug, through electrostatic interaction resulting in the formation of the Au 800 ‐CTAB‐PAA‐PEG‐AA.EPI complex. The findings confirmed that the chemotherapeutic agent was released on a pH‐dependent basis, that nuclear trafficking of EPI was assisted, and that antiproliferative effects in PC‐3 cells were induced [100].…”
Section: Application Of Hybrid Nps Against Different Type Of Cancersmentioning
confidence: 53%
“…Cell necrosis (NE) is an unscheduled process of cell death, characterized by cytoplasmic expansion, severe organelle damage and plasma membrane rupture. 63 It leads to the release of cell contents and inflammation. The PTT effect is due to the LSP resonance of gold nanoparticles.…”
Section: The Killing Mode Of Pdt On Tumor Cytokinesmentioning
confidence: 99%
“…connected to a collimator delivered laser radiation. Tumors established in mice flanks were subdivided into eight treatment groups (n ¼ 4/group), for a total of 32 subcutaneous tumors [20,36,37]. Four groups injected with GNRs underwent NIR-laser exposure according to: (a) GNRs (AR ¼ 4.1)injected tumors, laser irradiation at k ¼ 808 nm, (b) GNRs (AR…”
Section: Laser Irradiationmentioning
confidence: 99%